2021
DOI: 10.3389/fnagi.2021.593898
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Deterioration Pattern During Alzheimer's Disease Progression: A Regions-of-Interest Based Surface Morphometry Study

Abstract: Accurate detection of the regions of Alzheimer's disease (AD) lesions is critical for early intervention to effectively slow down the progression of the disease. Although gray matter volumetric abnormalities are commonly detected in patients with mild cognition impairment (MCI) and patients with AD, the gray matter surface-based deterioration pattern associated with the progression of the disease from MCI to AD stages is largely unknown. To identify group differences in gray matter surface morphometry, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 60 publications
4
31
0
Order By: Relevance
“…With regard to the extent of the identified WM changes, according to the effect size (Cohen's d values), these changes were mild or moderate. Despite this modest magnitude, the trend of these changes is consistent with common findings in the neuroimage literature regarding changes detected in a wide range of pathologies, such as schizophrenia [50][51][52], Alzheimer's disease [53][54][55], Parkinson's disease [56][57][58], or migraine [11,12,18]. In these disorders, lower FA values and higher MD, RD or AD have been identified in the patient groups compared to healthy controls.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to the extent of the identified WM changes, according to the effect size (Cohen's d values), these changes were mild or moderate. Despite this modest magnitude, the trend of these changes is consistent with common findings in the neuroimage literature regarding changes detected in a wide range of pathologies, such as schizophrenia [50][51][52], Alzheimer's disease [53][54][55], Parkinson's disease [56][57][58], or migraine [11,12,18]. In these disorders, lower FA values and higher MD, RD or AD have been identified in the patient groups compared to healthy controls.…”
Section: Discussionsupporting
confidence: 88%
“…These results coincided with several previous studies. A recent study showed that the cortical thickness and sulcus depth indices were significantly changed during AD progression, suggesting that gray matter characteristics can track AD progression ( Wu et al, 2021 ). Similarly, another study demonstrated distinct patterns of gray matter atrophy associated with mild behavioral impairment in CN subjects ( Shu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These brain regions are at the center of many brain function networks and are closely related to the progression of AD ( 22 ). As the condition develops, the functional connectivity of the above brain areas is gradually weakened ( 23 ).…”
Section: Discussionmentioning
confidence: 99%